Peranan Hakim Pengawasan dan Pengamat dalam Pelaksanaan Pembebasan Bersyarat di Masa Covid-19 - Apolinaris Hadiwikarta (MLJ Merdeka Law Journal, 2022)
Supervisory judges and observers judges are appointed for two years Specifically to supervise and observe inmates while Serving their sentences in correctional institutions as the implementation of the judge's decision, regarding the behavior of inmates and officers towards the inmates. The granting of parole during the Covid-19 is regulated in the regulation of the Minister of Law and Human Rights of the Republic of Indonesia No. 10 of 2020 concerning the Conditions of granting assimilation and integration rights for Convicts and children in the context of preventing and overcoming the spread of covid-19. The legal research used is empirical legal research, means data obtained from Supervisory judges and observers as the first Source through field research, which was carried out by observation. Supervisory judges and observers have no role in the parole process. Policies the implementation of parole during covid-19, Supervisory judges and observers make visits to the class 11 B detention Center to inform the inmates who are eligible to get parole during Covid-19. In carrying out their duties, they cannot work optimally, there are many shortcomings that occur in Various ways that hinder the workDOI: https://doi.org/10.26905/mlj.v3i1.7926